Pemanfaatan Media Pembelajaran Bahasa Arab Di Sekolah Kalamullah Al-Qur’an And Multilingual School Thailand - Deprizon; Salsabila, Adilah; Niah, Siti; Okmayura, Finanta (LPPM UMRI, 2024)
Arabic learning literacy at Kalamullah Al-Qur'an and Multilingual School, Pattani, Thailand is currently still lacking. For learning time is carried out only 1x a week. Therefore, there is a need for a medium to increase the attractiveness or interest of students in learning. The media used is in the form of recognizing letters and numbers in Arabic. The use of this media uses calligraphy writing made by madrasah ibtidaiyah teacher education students who carry out the International School Field Program in Pattani, Thailand. After an evaluation was carried out with the use of this Arabic introduction learning media, an increase in the post test was obtained by 22,16%, so as to increase students' interest in learning this Arabic introduction.